OPTIMALISASI PEMANFAATAN MEDIA KOMUNIKASI DALAM PROGRAM PENDAMPINGAN PEMBIASAAN MASYARAKAT PADA MASA COVID-19 DI LINGKUNGAN GERDU KELURAHAN GIRIPURWO KECAMATAN WONOGIRI KABUPATEN WONOGIRI - Nadhiroh Binti; Bayyidh Islamadin (LPPM STAIMAS WONOGIRI, 2021)
The implementation of Community Service (PKM) is an inseparable component of the Tri Dharma of Higher Education. During the Covid-19 pandemic, lecturers still have the responsibility to carry out community service. Together with students, lecturers can coordinate to carry out service through various programs. One of them is by assisting the habituation of the community during the Covid period. As members of the community, lecturers and students are required to be able to make a real contribution either through energy, thought or time. Even with various limitations for face-to-face meetings, they still have to try to contribute to the surrounding environment. Various communication media are used to provide information and assistance to the community. This article examines how to optimize the use of communication media in the Community Familiarization Assistance Program during the Covid-19 Period in the Gerdu Environment, Giripurwo Village, Wonogiri District, Wonogiri Regency. This research uses qualitative methods with descriptive analysis. Data obtained through documentation and observation. During the Covid-19 period, they can continue to work by adjusting the conditions in their respective regions. Some of the activities that can be carried out include maximizing the use of communication media for socializing about Covid-19 and health protocols on social media, at mosques, patrol posts and so on.